A Novel Grid Connected Photovoltaic System - Ali Rahnamaei; Mahdi Salimi (Institute of Advanced Engineering and Science, 2016)
Inthispaper, a novel grid connected photovoltaic system is proposed which can function as an Active Power Filter (APF) with Maximum Power Point Tracking (MPPT). Filter reference current is derived using Fourier Transform. Considering 33% reduction in inverter switches, cost of the grid-connect photovoltaic power plant can be reduced considerably. Using this approach, it is also possible to compensate for reactive and harmonic components of the local loads; moreover it can inject generated active power into grid at maximum power point of the photovoltaic cells. According to this, during daytime, the proposed system injects active power to the grid and at the same time compensates for the reactive power of the load. When there is no sunlight, the inverter only compensates local loads. Considering cost reduction, such capabilities may result in more application of the grid connected photovoltaic systems. Main novelty of the proposed system is simultaneous APF and MPPT functioning using single DC/AC converter. In fact, extra DC-DC converter is not required in the proposed system for MPPT. In order to verify the performance of the proposed method, some simulation is done using MATLAB/Simulink software. Also, some experimental results are presented for practical verification of the proposed grid connected inverter.